Effect on microstructure of TiO2 rate in Al2O3-TiO2 composite coating produced using plasma spray method - Islak, S.; Buytoz, S.; Ersoz, E.; Orhan, N.; Stokes, J.; Hashmi, M. Saleem; Tosun, N. (Natl Inst Optoelectronics, 2012)
In this study, Al2O3-TiO2 composite coatings were thermally sprayed on the SAE 1040 steel using atmospheric plasma spray (APS) process of mixed different rates micron sized TiO2 and micron-sized Al2O3 powders. The effects of TiO2 addition on the microstructure, phase compositions and microhardness of the coatings were investigated by using scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray diffractometry (XRD) and microhardness tester. The results show that the Al2O3-TiO2 composite coatings consists of both fully melted regions and partially melted regions, and the fully melted region has a lamellar-like structure. Phase transformations from mainly stable alpha-Al2O3 and anatase-TiO2 in the powders to predominant metastable gamma-Al2O3, rutile-TiO2 and Al2TiO5 phase in the Al2O3-TiO2 composite coatings were observed. It was determined that the pore content decreased with the increased in the TiO2 powder rate. The microhardness of the coating layers was 3-4.5 times higher than substrate material. The average microhardness values of the coatings were found to reach 650-860 HV.
Keywords: Plasma spray; Ceramic coating; gamma-Al2O3; Rutile-TiO2